WAKTU DALAM PERSPEKTIF AL-QURAN PADA AYAT-AYAT QASAM - Anam, Khoirul (ULUL ALBAB Jurnal Studi Islam, 2007)
Worldly life is usually related to time and space. The concept of time is central to the Holy Qur'an. That is why, Allah vows using several time-related concept like Ashr, Subh, Dhuha, uiil, Nahar. Using library review method, this research attempts to discover the meanings behind those above-mentioned terms. It uncovers that Â dawn: time before sunrise which is enlightening moment for anybody to wake up from lengthy sleep in order to prepare self to seek out Allah's bounty. Dhuha, when the sun is about. to rise to shine the world which can be meant a beginning of lifelihood so that anybody should welcome it with great joyfulness. Nahar, a mid day time when the sun shines fully and the men conduct their daily activities seeking His bounties. Ashar, end of the day when people start taking a rest from their daily activities. Lail, i.e night time after the sun has completely set when people relax after doing their job. It is when tranquility and peacefulness prevail human' s lifelihood which are of great of magnitude for development and the growth of their spiritual and physical well-being.